2012
DOI: 10.1039/c2cc30844d
|View full text |Cite
|
Sign up to set email alerts
|

Oxo-ester mediated native chemical ligation on microarrays: an efficient and chemoselective coupling methodology

Abstract: We report a highly efficient and selective method for the coupling of peptides and glycoconjugates bearing N-terminal cysteines to activated surfaces. This chemoselective method generates stable amide linkages without using any thiol additives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 36 publications
(31 reference statements)
0
38
0
Order By: Relevance
“…19 Weissenborn et al described OMNCL on oxo-ester activated surfaces and found 2,3,4,5,6-pentafluorophenyl (PFP) to be more efficient than p NP and N -hydroxysuccinimide (NHS) activating agents. 20 …”
Section: Introductionmentioning
confidence: 99%
“…19 Weissenborn et al described OMNCL on oxo-ester activated surfaces and found 2,3,4,5,6-pentafluorophenyl (PFP) to be more efficient than p NP and N -hydroxysuccinimide (NHS) activating agents. 20 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, mannosidic glycoamino acids are of interest as ligands for mannose-specific lectins in solution [17] as well as for the fabrication of glycoarrays on solid support [10,1819]. Moreover, we are interested to advance glycoamino acid deriatives such as 3 into ligands that can be “switched” between two states by oxidation/reduction.…”
Section: Resultsmentioning
confidence: 99%
“…This is an attractive concept, because it can be combined with solid-phase peptide synthesis (SPPS) [45], as well as with native chemical ligation (NCL) utilizing an S → N acyl shift [3,610]. In addition, glycocysteine derivatives can be easily converted into the corresponding dimers by oxidiation of the cysteine moiety into the respective cystine form.…”
Section: Introductionmentioning
confidence: 99%
“…In the case that the E → Z isomerisation process is high-yielding and the lifetime of the ( Z )-form of the azobenzene glycoside is long enough, it can be employed in bacterial adhesion assays independently from the more stable ( E )-isomer. Eventually, this type of azobenzene mannobioside can be further functionalised to be attached to various supports such as oligofunctional core molecules [15] or surfaces, to achieve switchable adhesive surfaces in continuation of our work on glycoarrays [1618] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%